Efektivitas Kebijakan Fiskal terhadap Permintaan Agregat dan Pertumbuhan Ekonomi di Indonesia: Studi Literatur 2020-2024 - Mutia Rafa Nursawitri; Nadia Sulistyaningsih; Miranda Herdia Nova; Miftahul Jannah; Khanaya Isyabrina Maryam; Gregorius Agung Steven Simanjuntak; Ahmad Setiawan Nuraya (Journal of Innovative and Creativity, 2025)
The purpose of this study is to investigate the impact that Indonesia's fiscal policy has had on aggregate demand and economic growth throughout the course of the period stretching from 2020 to 2024. The issue that is being discussed is the manner in which fiscal policy, which includes both taxation and spending by the government, can contribute to the economic recovery that follows a pandemic. This research makes use of a methodology known as a literature review, which involves the examination of a variety of publications, reports, and statistical data that are associated with the subject matter. Based on the data, it can be concluded that the expansive fiscal policy that the Indonesian government has enacted helps to effectively enhance aggregate demand, which ultimately results in improved economic growth. As a result of this discovery, a conversation is sparked on the significance of boosting collaboration between fiscal and monetary policy, as well as improving the effectiveness of subsidies and incentives for critical industries. Taking into account the issues that the global economy is currently facing, this research highlights the importance of having an efficient fiscal policy in order to foster growth and ensure the stability of the national economy.